Influence of emotional and spiritual intelligence from the National Education Philosophy towards language skills among secondary school students. - Saidy, Endang Pertiwi; Hassan, Aminuddin; Abd. Rahman, Fadzilah; Ab. Jalil, Habibah; Ismail, Ismi Arif; Krauss, Steven Eric (EuroJournals, 2009)
Emotional and Spiritual Intelligence (ESI) is a key element in providing guidelines towards an individual's achievement especially students. One's level of intelligence does not depend only on their level of intellectual intelligence. In fact it also depends on emotional and spiritual intelligence which is seen as the element that could influence a student's level of achievement. ESI is also able to influence improvement of students' value in order to produce a balanced individual as objectified by the National Education Philosophy (FPK). This paper discusses the importance of emotional and spiritual intelligence from the National Education Philosophy towards language performance of secondary school students. Five dimensions of emotional intelligence by Goleman (1998) namely aspects of self-awareness, self-control, motivation, empathy and social skills are being discussed in this study. Other than that, the adaptation suitability of Integrated Spiritual Intelligence Scale (ISIS) questionnaire introduced by Amram and Dryer (2007) for the purpose of measuring spiritual intelligence would also be discussed. The awareness of the needs to enhance secondary students' language skills through emotional and spiritual balance should be given emphasis in the current educational system.